Comprehensive review on sensitivity determination in fiber bragg grating accelerometer - Nazir, Abbas; Mohd Firdaus, Hassan (Akademi Baru, 2025)
Achieving accurate sensitivity measurements in Fibre Bragg Grating (FBG) sensors is crucial for their reliable application across various fields. This review paper delves into the sensitivity characteristics of FBG sensors, emphasizing the importance of precision in sensitivity determination. Various models and approaches for FBG strain, temperature, pressure, displacement and acceleration sensors have been examined. Among these, FBG acceleration sensors (FBG accelerometers) present the most significant challenge due to the dynamic nature of the measured acceleration in terms of both magnitude and frequency. Studies have shown that sensitivity in these sensors is inherently frequency-dependent. The assumption of linear sensitivity within one- third or one-half of the resonant frequency can be improved through advanced methods, including machine learning techniques. By analysing both theoretical and experimental studies, this review highlights the critical factors affecting sensitivity accuracy and identifies areas where discrepancies may arise. The aim of the review is to provide a thorough understanding of the methods for achieving accurate sensitivity measurements in FBG accelerometers, thereby guiding future research and development in this domain.